Fair Trade: What Does It Mean and Why Does It Matter? - Miller, David (Journal of moral philosophy, 2017)
The paper begins by locating the issue of trade within the broader literature on international and global justice. It then sets out eight different conceptions of ‘fair trade’, and examines the principles that lie behind them. They fall into three broad categories: procedural fairness accounts, which apply principles of equal treatment to the international rules under which trade takes place; producers’ entitlement accounts, which claim that trade must be structured so that all participants are safeguarded against harms such as exploitation or poverty; and fair exchange accounts, which require trade to be conducted on terms that produce a particular division of resources or benefits between the trading partners. These conceptions are partly complementary, but may on occasion pull in different directions, requiring us to reflect on the relative weights we attach to different aspects of fairness in trade.